1993
DOI: 10.1364/josab.10.000817
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous coherent pulsations in standing-wave laser oscillators: stability criteria for homogeneous broadening

Abstract: The stability criteria for single-mode standing-wave laser oscillators in the homogeneously broadened limit are reported, and two types of criteria are distinguished. The first type (type 1) corresponds to the minimum value of the threshold parameter for which an infinitesimal perturbation away from steady state grows into an oscillatory solution. A second type (type 2) corresponds to the minimum value of threshold parameter for which large-amplitude oscillations do not decay to the steady-state solution. Unda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…4 It has also been shown that the longitudinal field variations associated with a standing-wave model result in an increased threshold for laser instability. 9 For the present stability criteria studies, we have developed a semiclassical model for a single-longitudinal-mode, homogeneously broadened, unidirectional ring-laser oscillator with a focusing-beam laser field. In this model, as in many practical laser oscillators, the beam diameter is a function of longitudinal position between the laser mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has also been shown that the longitudinal field variations associated with a standing-wave model result in an increased threshold for laser instability. 9 For the present stability criteria studies, we have developed a semiclassical model for a single-longitudinal-mode, homogeneously broadened, unidirectional ring-laser oscillator with a focusing-beam laser field. In this model, as in many practical laser oscillators, the beam diameter is a function of longitudinal position between the laser mirrors.…”
Section: Introductionmentioning
confidence: 99%